TAXATION IN THE FINANCIAL SERVICES SECTOR IN INDONESIA: POLICY ANALYSIS AND IMPLICATIONS FOR TAX COMPLIANCE AND INDUSTRY GROWTH - Al-Amin; Sangrila Puspita Dewi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This study examines tax policies in Indonesia's financial services sector and their implications for tax compliance and industry growth. The financial services sector, which includes banking, insurance, capital markets, and fintech, plays an important role in the national economy, so effective taxation policies are needed to support the industry's sustainability and competitiveness. Through a literature review approach, this study analyses various applicable tax regulations, implementation challenges, and the impact of these policies on taxpayer compliance behaviour and business growth dynamics. The results of the study show that transparent, fair tax policies accompanied by incentives can increase tax compliance and encourage innovation and expansion in the financial services industry. Conversely, regulatory complexity and high administrative burdens can reduce compliance rates and hamper sector growth. This study recommends the continuous evaluation and refinement of tax policies with the involvement of stakeholders to create a healthy taxation ecosystem that optimally supports the development of Indonesia's financial services industry.